Learning based on competencies to improve the academic performance of the history course in university students - Cáceres Ugarte, Yurkov K. (2022)
Among the most relevant academic problems in a university educational context, it is related to the lack of learning methodologies and strategies that the teacher must teach in the classroom, therefore, it is preponderant to develop competency-based learning. The objective was to determine how competency-based learning improves the academic performance of the History of Peru course in the students of the 1st cycle of the Law School of the University of Huánuco. The quantitative type was considered, the explanatory level and the design is quasi-experimental, where the pre-test and post-test were applied in the control and experimental groups. The population consisted of a total of 73 students. The technique used was observation, and the data collection instrument was the "rubric". The results showed that 87.4% of the students in the experimental group achieved passing grades, while in the control group this difference is not very significant. It was concluded that competency-based learning significantly improves academic performance in the Peruvian history course in law school students.